2018
DOI: 10.1080/17530350.2018.1481877
|View full text |Cite
|
Sign up to set email alerts
|

Workfulness: governing the disobedient brain

Abstract: The Scandinavian telecommunication company Telenor recently introduced the notion of Workfulness by adapting digital detox to the workplace. Workfulness is a management program aimed at technologyintensive companies that rely strongly on digital media. The program encompasses strategies of disconnection for employees, including mobile and email-free work hours and technology-free meetings, in order to enhance focus and efficiency. This article investigates Workfulness as one prominent example of managerial app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 39 publications
(38 reference statements)
0
27
0
1
Order By: Relevance
“…As any cultural trend or counter-trend, digital detox draws on a variety of inspirations, and motives for practicing digital detox vary. In one sense, digital detox fits within a tradition of corporate self-optimization where individuals are encouraged to improve efficiency through the use of technology and software, including software to reduce digital distractions (Gregg, 2015; Guyard and Kaun, 2018). Furthermore, as noted, digital detox draws on notions of balance and mindfulness.…”
Section: Digital Detox – a New Termmentioning
confidence: 99%
“…As any cultural trend or counter-trend, digital detox draws on a variety of inspirations, and motives for practicing digital detox vary. In one sense, digital detox fits within a tradition of corporate self-optimization where individuals are encouraged to improve efficiency through the use of technology and software, including software to reduce digital distractions (Gregg, 2015; Guyard and Kaun, 2018). Furthermore, as noted, digital detox draws on notions of balance and mindfulness.…”
Section: Digital Detox – a New Termmentioning
confidence: 99%
“…For some informants, time management through self-regulation relied on willpower as the sole strategy: deciding, repeatedly, to not (extensively) use the smartphone, and then do as decided, every time. However, many appeared to subscribe to the view, described in other studies, that willpower does not suffice to control digital media use (Guyard and Kaun, 2018). They, therefore, added different supplementary strategies: managing settings describes doing something with the smartphone to make it less intrusive, such as turning off notifications.…”
Section: Conflicting Responsibilities: Time Management Strategies Amentioning
confidence: 99%
“…They "specified certain quantities of digital technology use as unhealthy, comparing them to problematic eating behaviours." It also conveys a special effort from the individual-or services offered to them-that needs to be done, as the brain seems "disobedient" in face of technology (Guyard & Kaun, 2018).…”
Section: Disconnection Rhetoricmentioning
confidence: 99%
“…In her ethnography on digital detox camps around San Francisco, California, Sutton found that detoxers felt they learned not only to live better with technology but also to reconnect with themselves by appreciating privilege, and with others in deeper connections. They “specified certain quantities of digital technology use as unhealthy, comparing them to problematic eating behaviours.” It also conveys a special effort from the individual—or services offered to them—that needs to be done, as the brain seems “disobedient” in face of technology (Guyard & Kaun, 2018).…”
Section: Digital Disconnectionmentioning
confidence: 99%